These Extremes : Poems and Prose - Bausch, Richard, 1945- (Book collections on Project MUSE., 2009)
In his first collection of poetry and prose, award-winning fiction writer Richard Bausch proves that he is also an accomplished poet. Penned over a span of many years, the poems in These Extremes deal with a wide variety of subjects. Many focus on Bausch's own family and relationships. In one long, touching poem, "Barbara (1943-1974)," the poet memorializes his oldest sister, who died young. He also offers two prose memory pieces, recollections from his childhood and adolescence. In these brief "essays," Bausch draws loving but unsentimental portraits of his father, mother, and other relatives.